ANALYSIS OF THE ‘CONFLICT’ BETWEEN WOMEN OF EASTERN NIGERIA AND THE COLONIAL AUTHORITIES: A PEACEBUILDERS’ PERSPECTIVE - ONUOHA, Austin; UZODINMA, Amaka (Socialscientia: Journal of Social Sciences and Humanities, 2020)
The year 2019 marks the 90th anniversary of the misunderstanding over bad governance, discrimination and marginalization between the women of Eastern Nigeria and the colonial authorities. History looks at the past with a view to understanding the present while preparing for the future. Unfortunately, as the world commemorates this epochal event, an aspect that has been missing is what lessons we can learn from the events especially as it relates to peacebuilding. This is more so that this event was never celebrated in Nigeria as a reminder of Nigeria’s journey and evolution to nationhood. More disturbing is the proclivity towards the celebration of violence as a means of acknowledging the contributions of women to nation-building. This paper is aimed at revisiting and may be putting some of these into proper perspective with a view to learning lessons for peacebuilding. The paper examines the implications and lessons of the context and nomenclature of violence on response using “the conflict between Women of Eastern Nigeria and the colonial authorities” as a case study. This study employs the peacebuilding approach which emphasizes nonviolence as its over-arching framework. We concluded that using a peacebuilding approach in analysing the conflict would have produced enduring lessons for addressing such a disagreement in future while avoiding a resort to violence